POLITICS MILITARY IN POST – NEW ORDER INDONESIA - AMANAH, RIFQA DENI; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Post New Order Indonesian Politics which emphasize of changes in military problems in politics. Especially in the Indonesian Government. Civil-Military System that still overlap in politics. That is caused from the larger role of the military in Indonesia during The New Order.This research have to look at the changing role and function of the military who make changes like Redefinition, Repotioning, and Reactualitation. Along with research the factors that influence of changes in the Government transition procces in post-New Order in Indonesia.Basis of analysis research it can be concluded that Indonesia military is always undergoing a procces of change in the each government transition. So that military politics always has a different system and adapted according to the prevailing system of government. Indonesia’s government in politics has not been able break away from the military, is caused because a several factors, especially on the weak civilian control and professional moral value that always different allowing to the comprehension of the military institution itself.Keywords : Government Transition, Politics, Military Politics